ISIS: a genetic algorithm based technique for custom on-chip interconnection network synthesis - Srinivasan, K.; Chatha, K.S. (18th International Conference on VLSI Design held jointly with 4th International Conference on Embedded Systems Design, 2005)
On-chip packet switched interconnection networks (or network-on-chip (NoC)) have been proposed as a solution to the communication challenges of system-on-chip (SoC) design in the nanoscale regime. SoC design offers the opportunity for incorporating custom NoC architectures that are more suitable for a particular application, and do not necessarily conform to regular topologies. This paper presents ISIS, a novel genetic algorithm (GA) based technique for custom NoC synthesis that optimizes both the power consumption and area of the design subject 10 the performance constraints, and generates a custom NoC topology and mapping of the communication traces on the architecture. ISIS solves a multi-objective optimization problem by minimizing a cost function expressed as a linear combination of the cost incurred due to power consumption and area. We present a detailed analysis of the quality of the results and the solution times of the proposed technique by extensive experimentation with realistic benchmarks and comparisons with optimal MILP solutions.